Pengaruh Model Pembelajaran Mind Mapping Terhadap Keaktifan Belajar Siswa Pada Muatan Materi PPKn Di Kelas IV SDN 4 Praya - Marthasari Indraayu; Khairunnisa Khairunnisa; Ilham Syahrul Jiwandono (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This study aims to determine the effect of the mind mapping learning model on student learning activities on the content of PPKN material in class IV SDN 4 Praya. The type of research used in this research is quantitative research with a quasi-experimental design method. The population in this study were 88 students, and the sample was an experimental class with 30 students and a comparison or control with 30 students. The technique used to collect data is observation and documentation. The data obtained were analyzed using normality test, homogeneity test and t-test. The results of this study indicate that there is an effect of the mind mapping learning model on student learning activities on the content of the PPKN material in class IV, which can be seen in the comparison of the value of 3.310 which is greater than with db = 58 at the significance level of 5% (0.05) which is 1.996 . And at (2-tailed) of 0.000. The value (2tailed) is 0.000 <0.05, so the hypothesis in this study is that there is a significant effect of the Mind Map learning model on student learning activities on the content of the fourth grade Civics Education material at SDN 4 Praya.